2012
DOI: 10.5120/4870-7297
|View full text |Cite
|
Sign up to set email alerts
|

Voice Recognition and Authentication as a Proficient Biometric Tool and Its Application in Online Exam for P.H People

Abstract: Voice Recognition is a fascinating field spanning several areas of computer science and mathematics. Reliable speech recognition is a hard problem, requiring a combination of many complex techniques; however modern methods have been able to achieve an impressive degree of accuracy. On the other hand, today, most of the companies or institutes are conducting their examinations online to be a part of this best ever growing world. In this system user can give any available examination at any accessible center as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…Other physiological parameters available in the field of biometrics include vein recognition [24], ear recognition [25], palm print recognition [26], hand geometry [27], finger geometry [28], lip furrows [29,30], DNA [31], and odour/scent recognition [32]. Behavioural parameters that can be useful in biometric-detection of an individual include keyboard dynamics [33], gait [34], voice recognition [35], and signature [36,37].…”
Section: Other Methodsmentioning
confidence: 99%
“…Other physiological parameters available in the field of biometrics include vein recognition [24], ear recognition [25], palm print recognition [26], hand geometry [27], finger geometry [28], lip furrows [29,30], DNA [31], and odour/scent recognition [32]. Behavioural parameters that can be useful in biometric-detection of an individual include keyboard dynamics [33], gait [34], voice recognition [35], and signature [36,37].…”
Section: Other Methodsmentioning
confidence: 99%
“…Few researchers have also focused on authenticating along with recognizing an individual's voice by comparing the collected voice template for training and testing [27,28]. However, architecture performance was not reported for noisy or real-time environments.…”
Section: Related Workmentioning
confidence: 99%
“…For physically challenged people who can use their voice only to register and attend the examination, one way to conduct online examination was offered in [11]. Here an efficient spectrum analysis to continuous-time signal based on DFT, the Fast Fourier Transform (FFT) method was adopted for authentication of voice and concluded that The Fast Fourier Transform (FFT) was a much faster mathematical algorithm which eliminates redundant calculations in the Fourier Transform and was therefore much speedier.…”
Section: Feature Extraction Techniques 21 Fast Fourier Transform (Fft)mentioning
confidence: 99%